The yesterday and today of the european language portfolio Iin Turkey - Ilknur Pekkanli Egel, (Penerbitan UKM, 2009)
Concern for research in this area stems from the point that Turkey since 2001 has taken part in the piloting phase of the European Language Portfolio. After the piloting phase, the Ministry of Turkish National Education has decided to officially launch the European Language Portfolio in the academic year of 2009-2010. In Turkey, Ankara University and Bilfen Schools have also developed European Language Portfolio models and have had these models validated by the Council of Europe. The purpose of the present study is to investigate the development of European Language Portfolio models in Turkey. Firstly, the background of the situation on the formation of the European Language Portfolio by the Council of Europe is addressed. Secondly, the origin of the European Language Portfolio within the Turkish national education system is described. The next section dwells upon the issues relating to the present stage of European Language Portfolio implementation in Turkey. Positive outcomes of European Language Portfolio implementation in other Member States are shortly addressed. Finally, while the study illustrates that the European Language Portfolio has proved to be an important innovation in foreign language learning, the implementation change in Turkey necessitates sustained effort to promote the concepts of the European Language Portfolio so as to reach long lasting effects